The Cultural Limits of Challenging Hegemonic Masculinity: Critical Analysis of Online Responses to Axe Turkey Advertisements - NAS, ALPARSLAN (My University, 2021)
Hegemonic masculinity has been a challenging concept in cultural studies since the 1990s. Throughout the past three decades, the concept has been carefully applied to the critical analysis of gender in several academic fields, including media studies. Many studies have defined hegemonic masculinity as a locally significant and dynamic concept that is open to various interpretations across different cultural representations and experiences. This article offers a culturally specific analysis of the representations and receptions of hegemonic masculinity in Turkish advertising discourse. For this purpose, this article analyzes Axe Turkey’s two advertisements that were released for International Women’s Day in 2018. The advertisements challenged hegemonic masculinity in Turkish culture by carrying critical narratives. The advertising discourse met with a variety of audience responses through online comments. Content analysis of the online responses revealed a dominant trend in the audiences towards restoring the hegemonic masculine order by applying several discursive strategies against the advertising narrative.
Keywords: advertising; content analysis; discourse; hegemonic masculinity; Turkey